2021
DOI: 10.1021/acsaelm.1c00516
|View full text |Cite
|
Sign up to set email alerts
|

POx/Al2O3 Stacks for c-Si Surface Passivation: Material and Interface Properties

Abstract: Phosphorus oxide (PO x ) capped by aluminum oxide (Al2O3) has recently been discovered to provide excellent surface passivation of crystalline silicon (c-Si). In this work, insights into the passivation mechanism of PO x /Al2O3 stacks are gained through a systematic study of the influence of deposition temperature (T dep = 100–300 °C) and annealing temperature (T ann = 200–500 °C) on the material and interface properties. It is found that employing lower deposition temperatures enables an improved passivation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 67 publications
0
17
0
Order By: Relevance
“…The origin of the low D it enabled by PO x /Al 2 O 3 on silicon is found to be related to surface passivation provided by hydrogen and the formation of AlPO 4 upon annealing, leading to a decrease in D it by almost orders of magnitude from ~10 13 to ~10 10 eV − 1 cm − 2 [47]. On silicon a 100) wafers (data points with solid lines) and wurtzite InP nanowires (data points with dashed lines), as a function of annealing temperature (10 min in N 2 ), together with unpassivated semiconductor surfaces as reference.…”
Section: Overview Of D It and Q Fmentioning
confidence: 95%
See 4 more Smart Citations
“…The origin of the low D it enabled by PO x /Al 2 O 3 on silicon is found to be related to surface passivation provided by hydrogen and the formation of AlPO 4 upon annealing, leading to a decrease in D it by almost orders of magnitude from ~10 13 to ~10 10 eV − 1 cm − 2 [47]. On silicon a 100) wafers (data points with solid lines) and wurtzite InP nanowires (data points with dashed lines), as a function of annealing temperature (10 min in N 2 ), together with unpassivated semiconductor surfaces as reference.…”
Section: Overview Of D It and Q Fmentioning
confidence: 95%
“…Data on InP nanowires were adapted from Black et al [49] Note that the reported carrier lifetimes on Si were determined using photoconductance decay, while the carrier lifetimes on InP NWs were determined using time-resolved photoluminescence. high positive fixed charge of around 10 12 -10 13 cm − 2 is present, both after deposition and after annealing [47]. On InP NWs, PO x /Al 2 O 3 stacks induce an n-type field-effect, which indicates the presence of positive fixed charges [95].…”
Section: Overview Of D It and Q Fmentioning
confidence: 99%
See 3 more Smart Citations